Analisis Penerapan Etika Bisnis Islam Dalam Proses Pembuatan ‎Tempe Di Desa Resam Lapis ‎ Kec. Bantan Kab. Bengkalis ‎ - M. Fadil Iqbar; Nazri; Nurulia Ramadhani; Zulfikar Hasan (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This research was conducted with the aim of finding out how tempe management is viewed from the perspective of Islamic business ethics for tempe entrepreneurs in Resam Lapis Village. The research location will be carried out at Home Industry which is in Resam Lapis Village, Bantan District. The type of research carried out is field research. The research approach used in this research is descriptive qualitative. The population that will be taken in this study is all tempe production houses in Resam Lapis Village. In collecting data, the method that the author uses is observation by going directly to the tempe-making home industry to observe directly, interviews conducted directly with the owners of the tempe-making home industry and collecting documentation from interviews and observations in the form of writing, photos, archives, and so on related to the application of Islamic business ethics carried out by the tempe-making home industry. This study uses qualitative data analysis methods. Qualitative analysis is an effort made by working with data, finding patterns, sorting it into manageable units, determining what is important and what is learned and deciding what others can tell. The results of the study found that the implementation of Islamic business ethics in Home Industry Tempe Nursiah has been implemented, namely the principle of unity, the principle of free will, the principle of responsibility and the principle of truth (virtue and honesty). However, there is one principle that is not implemented, namely the principle of equilibrium.